Gaya Kepemimpinan, Budaya Organisasi dan Organisasi Pembelajar dalam Membentuk Kepuasan Kerja Karyawan - Ahmad Adriansyah; Adi Subrata (STIE Indonesia Banking School, 2017)
Job satisfaction is an important factor in human resources management in an organization. There are three factors that can influence job satisfaction. There is leadership style, learning organization and corporate culture. Leadership style and corporate culture are also can influence learning organization. Research conducted in bank X, one of commercial banking in Indonesia. The sample size is 242 employee, and the model tested by Structural Equation Modeling (SEM). The result shows that learning organization and corporate culture significantly influence employee’s job satisfaction. Leadership style and corporate culture significantly influence learning culture.